QUANTIFICATION AND CLASS! FICA TION OF MICRO POROSITY IN A MIOCENE CARBONATE PLATFORM OF CENTRAL LUCONIA, OFFSHORE SARA WAK, MALAYSIA AND ITS EFFECTS ON RESERVOIR PROPERTIES - RAHMAN, MD HABIBUR (2011)
The effects of microporosity on carbonates have been addressed in numerous publications; there is, however, almost no published literature on microporosity in the Miocene carbonates of Southeast Asia. This study aims at quantifying, and classifying microporosity in the Miocene carbonate reservoirs of Central Luconia, offshore Sarawak and at assessing its effects on reservoir properties. Digital Image Analysis (DIA) of thin sections and scanning electron microscope (SEM) images are useful tools to quantify porosity in reservoir rocks. DIA technique uses thin section images taken under polarizing microscope, fluorescence microscope, and scanning electron microscope to estimate the amount of microporosity present in carbonate reservoirs. The quantification of microporosity leads to determining its empirical relationships with permeability and sonic velocity. These relationships can be used for a better understanding of the reservoir system. This study on the Miocene carbonate reservoirs of Central Luconia, offshore Sarawak, Malaysia revealed an inverse relationship between microporosity and permeability. Permeability in the Miocene carbonate reservoir is reduced with an increase in microporosity at different depths in the same reservoir, characterized by the same amount of total porosity. The relationship between porosity and permeability in the Miocene carbonate reservoirs shows a better correlation when microporosity is considered and subtracted from the total porosity of the reservoir. Microporosity in the carbonate reservoirs of Central Luconia, offshore Sarawak, affects the elastic properties of the rock. Microporosity reduces the sonic velocity of the Miocene carbonate reservoirs. Microporosity can occur in grain, cement or matrix and it is related to the diagenetic history of the carbonate reservoirs. Depending on the crystallometry and morphometry of micrite particles, microporosity can vary both in amount and in nature (microporosity can reach up to 25% by volume of the rock or 80% of the total porosity of the reservoir).